Equivalence and Practice Effect of Alternate Forms for Malay Version of Auditory Verbal Learning Test (MAVLT) - Munjir, Norulsuhada; Othman, Zahiruddin; Zakaria, Rahimah; Shafin, Nazlahshaniza; Hussain, Noor Aini; Desa, Anisah Mat; Ahmad, Asma Hayati (IfADo - Leibniz Research Centre for Working Environment and Human Factors, Dortmund, 2015)
This study aims to develop two alternate forms for Malay version of Auditory Verbal Learning Test (MAVLT) and to determine their equivalency and practice effect. Ninety healthy volunteers were subjected to the following neuropsychological tests at baseline, and at one month interval according to their assigned group; group 1 (MAVLT - MAVLT), group 2 (MAVLT – Alternate Form 1 - Alternate Form 1), and group 3 (MAVLT - Alternate Form 2 - Alternate Form 2). There were no significant difference in the mean score of all the trials at baseline among the three groups, and most of the mean score of trials between MAVLT and Alternate Form 1, and between MAVLT and Alternate Form 2. There was significant improvement in the mean score of each trial when the same form was used repeatedly at the interval of one month. However, there was no significant improvement in the mean score of each trial when the Alternate Form 2 was used during repeated neuropsychological testing. The MAVLT is a reliable instrument for repeated neuropsychological testing as long as alternate forms are used. The Alternate Form 2 showed better equivalency to MAVLT and less practice effects